2020
DOI: 10.1590/198053146232
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of Physical Education According to Students From Germany and Chile

Abstract: Resumo O presente estudo tem o objetivo de determinar a forma como estudantes de diferentes culturas percebem a utilidade das aulas de Educação Física. Foram entrevistados 2.748 estudantes (1.373 da região da Araucanía, Chile; e 1.375 do Estado de Sarre, Alemanha). Tanto os alunos chilenos como os alemães reconhecem mais uma utilidade “esportivo-recreativa” que uma “socioeducativa”, e os chilenos apresentam valores mais altos que seus pares alemães; por outro lado, ambos os grupos manifestam seu desacordo com … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 14 publications
0
1
0
1
Order By: Relevance
“…The data displayed that respondents are comfortable teaching today's subject. Furthermore, it was found that the professional qualification of teachers is associated with students' attitudes toward the subject (Carcamo-Oyarzun et al, 2022;Sucuoglu and Atamturk, 2020;Zalech, 2021). On the other hand, the findings differ from what most people expected after examining other published scholarly papers.…”
Section: Promoting Physical Culture Inside the Campusmentioning
confidence: 75%
“…The data displayed that respondents are comfortable teaching today's subject. Furthermore, it was found that the professional qualification of teachers is associated with students' attitudes toward the subject (Carcamo-Oyarzun et al, 2022;Sucuoglu and Atamturk, 2020;Zalech, 2021). On the other hand, the findings differ from what most people expected after examining other published scholarly papers.…”
Section: Promoting Physical Culture Inside the Campusmentioning
confidence: 75%
“…En los estudios que consideran contextos urbanos y rurales, se observa que dos estudios se realizaron en Chile y el extranjero, considerando los países de Costa Rica y Alemania (Cárcamo-Oyarzún et al, 2017;Morales, 2019). Los dos estudios restantes se desarrollan en las regiones Metropolitana de Santiago y Araucanía (Castillo et al, 2016;Valdivia y Medina, 2014).…”
Section: Enfoque Educación Intercultural En Contextos Urbanos Y Ruralesunclassified
“…This, although at this age children are usually happy, means that they enjoy their PE lessons. Carcamo-Oyarzun [34] states that this fact is positive and contributes to their adherence to continued PA outside school. Generally speaking, and outside the different categories, it should be remembered that the ages of the participants are between 6 and 8 years old.…”
Section: Facial Expressionmentioning
confidence: 99%